2020
DOI: 10.3390/nu12020563
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Footsteps Using Connected Bracelets with the Timed Up-and-Go Test and the 6-Minutes Walking Test in a Prospective Colorectal Surgery Cohort

Abstract: Preoperative physical activity and early postoperative mobilization are key components of enhanced recovery programs but both difficult to assess. The aim of this prospective study was therefore to compare different ways to measure preoperative physical activity and to correlate those tests with postoperative physical activity (footsteps). The daily number of footsteps was recorded from preoperative day 5 to postoperative day (POD) 3 in a prospective cohort of colorectal patients using connected wrist bracelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Romain et al . showed that postoperative step counts were correlated with preoperative steps 61 . Kovar et al .…”
Section: Resultsmentioning
confidence: 95%
“…Romain et al . showed that postoperative step counts were correlated with preoperative steps 61 . Kovar et al .…”
Section: Resultsmentioning
confidence: 95%
“…The search strategy yielded a total of 1525 studies. Following deduplication, 1253 were screened, resulting in 104 studies for full text review, 20 of which were included in this review (Figure 1) [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Table 1 summarises key study characteristics.…”
Section: Study Demographicsmentioning
confidence: 99%
“…Significant correlations were identified between reduced postoperative physical activity and complication occurrence (OR 3.197, p = 0.039) and length of stay (β 4.068, p = 0.013). Another device used by Romain et al [23], the connected bracelets, assessed preoperative and postoperative physical activity. Preoperative step count was significantly associated with increased postoperative physical activity (r = 0.527, p < 0.001).…”
Section: Perioperative Datamentioning
confidence: 99%
“…A previous study showed that preoperative PA was associated with postoperative functional recovery in patients with gastrointestinal cancer 13 ) . Moreover, preoperative and postoperative steps have been moderately positively correlated in patients undergoing colorectal resection 14 ) . Therefore, it can be inferred that preoperative PA and postoperative ambulation are related in patients with gastrointestinal cancer and that postoperative delayed ambulation results in decreased postoperative PA and delayed functional recovery.…”
Section: Introductionmentioning
confidence: 99%